Índice de qualidade das águas na parte baixa da bacia hidrográfica do rio Trussu, Ceará - Palácio, Helba Araújo de Queiroz (2004)
The main goal of this work was to evaluate the water quality in the Trussu River valley. The Trussu River drainage an area of 1,590 km2 and it is a tributary of left site of Jaguaribe River. This region located in Iguatu County, Ceará, Brazil. Drainaged waters are stored at Roberto Costa (Trussu) dam, which deliver water to human consume, livestock and irrigation in the last 20 km of the valley. In this study, a data reduction technique, Principal Componente Analysis (PCA), was used to develop a water quality index. Water samples were carried out every month from sept./2002 to mar./2004 in nine sample stations spread out the Trussu River area. Five of them are sited along the river and other four are located in shallow wells. It was analyzed the following variables: pH, EC, Na+, Ca+2, Mg+2, K+, Cl-, HCO3 -, PO4 -2, NH+ 4, NO3 - , SO4 -2 and SAR. The use of PCA technique has allowed the identification of variables that explain higher percentage of total variance. Also, PCA technique allowed the reduction of the 13 variables to two significant components that explain 83.44% of the total variance. The first one, PC1, (account for 64.10% of the variance) which can initially assigned to water mineralization. The second one, PC2, (account for 19.34% of the variance) is built from variables indicative of man-made effect. In a second step, these parameters were applied to develop a water quality index (WQI). The WQI showed up a good adequacy to evaluate the water quality in Trussu River valley. Also, results pointed up that water quality to shallow well has a high spatial variability. Sampling stations 8 and 9 registered the lowest WQIs and they were inapt to human consume, where WQIs were lowed than 30. Surface waters presented as suitable to human consume during the studied period with WQIs average over to 80. the anthropeic degradation was observed in sampling stations 6 and 7, where WQIs are lower than other stations sited in up land. These results can be explained by a bigger demographic concentration close to stations and the lack of sewer in the region.